Hypertension in the South African public healthcare system: a cost-of-illness and burden of disease study. Issue 2 (22nd February 2022) - Kohli-Lynch, Ciaran N; Erzse, Agnes; Rayner, B; Hofman, Karen J
Abstract : Objectives: To quantify the health and economic burden of hypertension in the South African public healthcare system. Setting: All inpatient, outpatient and rehabilitative care received in the national public healthcare system. Participants: Adults, aged ≥20 years, who receive care in the public healthcare system. Outcomes: Worksheet-based models synthesised data from multiple sources to estimate the burden of disease, direct healthcare costs, and societal costs associated with hypertension. Results were disaggregated by sex. Results: Approximately 8.22 million (30.8%, 95% CI 29.5% to 32.1%) South African adults with no private health insurance have hypertension. Hypertension was estimated to cause 14 000 (95% CI 11 100 to 17 200) ischaemic heart disease events, 13 300 (95% CI 10 600 to 16 300) strokes and 6100 (95% CI 4970 to 7460) cases of chronic kidney disease annually. Rates of hypertension, hypertension-related stroke and hypertension-related chronic kidney disease were greater for women compared with men. The direct healthcare costs associated with hypertension were estimated to be ZAR 10.1 billion (95% CI 8.98 to 11.3 billion) or US$0.711 billion (95% CI 0.633 to 0.793 billion). Societal costs were estimated to be ZAR 29.4 billion (95% CI 26.0 to 33.2 billion) or US$2.08 billion (95% CI 1.83 to 2.34 billion). Direct healthcare costs were greater for women (ZAR 6.11 billion or US$0.431 billion) compared with men (ZAR 3.97 billion or US$0.280 billion). Conversely, societal costs were lower for women (ZAR 10.5 billion or US$0.743 billion) compared with men (ZAR 18.9 billion or US$1.33 billion). Conclusion: Hypertension exerts a heavy health and economic burden on South Africa. Establishing cost-effective best practice guidelines for hypertension treatment requires further research. Such research will be essential if South Africa is to make progress in its efforts to implement universal healthcare.